Extreme High Greenland Blocking Index Leads to the Reversal of Davis and Nares Strait Net Transport Toward the Arctic Ocean. Issue 17 (28th August 2021) - Myers, Paul G.; Castro de la Guardia, Laura; Fu, Chuanshuai; Gillard, Laura C.; Grivault, Nathan; Hu, Xianmin; Lee, Craig M.; Moore, G. W. K.; Pennelly, Clark; Ribergaard, Mads Hvid; Romanski, Joy
Abstract: Baffin Bay exports Arctic Water to the North Atlantic while receiving northward flowing Atlantic Water. Warm Atlantic Water has impacted the retreat of tidewater glaciers draining the Greenland Ice Sheet. Periods of enhanced Atlantic Water transport into Baffin Bay have been observed, but the oceanic processes are still not fully explained. At the end of 2010 the net transport at Davis Strait, the southern gateway to Baffin Bay, reversed from southward to northward for a month, leading to significant northward oceanic heat transport into Baffin Bay. This was associated with an extreme high in the Greenland Blocking Index and a stormtrack path that shifted away from Baffin Bay. Thus fewer cyclones in the Irminger Sea resulted in less frequent northerly winds along the western coast of Greenland, allowing anomalous northward penetration of warm waters, reversing the volume and heat transport at Davis Strait. Plain Language Summary: Baffin Bay exports cold and fresh Arctic Water to the North Atlantic while receiving northward flowing warm and saline Atlantic Water. This warm Atlantic Water has been shown to drive the retreat of tidewater glaciers. Periods of enhanced Atlantic Water transport into Baffin Bay have been observed. The oceanic processes that led to the enhanced transport of these warm waters into Baffin Bay are still not fully explained. Here we show from a combination of observational and model studies that at the end of 2010 the net transport at Davis Strait, the southern gateway to Baffin Bay, reversed from southward to northward for around a month, leading to significant northward oceanic heat transport into Baffin Bay. Anomalous winter winds kept the Atlantic Water on the West Greenland shelf, to propagate north into Baffin Bay instead of entering the interior Labrador Sea. At the same time, a mid‐level high pressure system sat over Greenland, efficiently preventing storms from reaching Baffin Bay. Anomalous winds also generated a positive transport signal that propagated cyclonically around Greenland, trapping warm waters on the West Greenland shelf, while also reversing the flow from the Arctic Ocean at Nares Strait. Key Points: Net transport through Davis and Nares Strait reversed from southward, in December 2010 to northward back toward the Arctic Ocean The transport reversal was driven by anomalous winter winds over the Labrador Sea The anomalous winds were associated with a record high of the Greenland Blocking Index and a change in the storm track